Accounting for inventories at enterprise as a component of information and communication system - B.L. Kyryluk; I.V. Suprunova (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The current trends in the formation of information and communication system in terms of the inventories as the most significant component of the assets of companies are researched in the article. The information and communication system of a company provides the flow of information among the participants by the information channels, the sequence and direction of transmission of the information to specific subjects in accordance with the tasks. The essence and place of the accounting policies as the component of information and communication system are researched. The directions of improvement of information provision regarding the inventories of a company are proposed, that can be implemented in connection with the improvement of accounting policies by specifying the type of communication system, the ways of providing feedback, the formation of information channels, the identification of measures to prevent the information noise in order to avoid information threats. The obtained results and worked out proposals in the article allow to develop the comprehensive information and communication system of an enterprise in terms of inventories in order of further researches, which, taking to account their characteristics, will improve the information inter-environment of a company and the quality of decisions on this basis.